Riba issues in gold investment and trading: practice of selected companies in Malaysia - Markom, Ruzian; Ibrahim@Musa, Hariati (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2013)
Gold was used as the most common form of money throughout history. Its role as currency is now replaced by the paper money, but gold has never stop from being the attention of human beings due to its special features that do not present in other commodities. People invest in gold because of various reasons including it is a hedge against inflation and carries an intrinsic and real value. Gold and fiat money are concluded by Muslim jurists as ribawi items therefore the dexchange or trading involving them is governed by two basic rules of Shariah i.e. must be of equal weight and the selling and buying must happen at one majlis. The objective of this paper is twofold. The first objective is to study the practice of gold trading in Malaysia and its compliance to the requirements of Shariah. At the same time, it is to provide readers and the stakeholders in gold trading i.e. banks, companies, gold dealers and customers with the Shariah requirements that they must adhere in this business. In meeting the objectives, a case study on the trading practice of selected companies and banks were conducted. The study adopted a qualitative approach by describing and exploring the Shariah issues surrounding the gold trading and investment in Malaysia. The findings showed that many companies involve in gold trading in Malaysia do not have a Shariah panel, thus some of their practice are not in compliance with the requirements of Shariah. This is due to the fact that the establishment of Shariah panel is not a legal requirement in gold trading. Hence, it is recommended that the Shariah Panel is compulsory for Shariah based gold investment and trading industries.